Edukasi Interaksi Obat–Makanan untuk Optimalisasi Terapi Pasien di Fasilitas Kesehatan - Rifa'atul Mahmudah (PT. Penerbit Riset Sadwa, 2025)
Drug–food interactions significantly influence therapeutic outcomes; however, many patients have limited understanding of their impact on drug absorption, effectiveness, and safety. Insufficient literacy regarding proper medication usage may lead to therapeutic failure, particularly among outpatients who frequently take medications together with certain foods or beverages. This community service program aimed to improve patient knowledge on drug–food interactions and the significance of medication timing through direct education supported by informational leaflets. The activity included target identification, material development, leaflet distribution, and one-on-one counseling for patients and caregivers at the Outpatient Pharmacy Waiting Area of Bahteramas General Hospital. The results showed strong participant engagement and an increased understanding of common drug–food interactions, appropriate medication timing, and potential risks associated with inappropriate use. This activity effectively enhanced patient literacy and treatment adherence. Therefore, brief educational interventions using interpersonal communication and visual media can serve as a sustainable strategy to improve medication safety within the community.